2019
DOI: 10.1093/nar/gkz1117
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 binds Alu-rich introns in SMN and promotes pre-mRNA circularization

Abstract: The Spinal Muscular Atrophy (SMA) gene SMN was recently duplicated (SMN1 and SMN2) in higher primates. Furthermore, invasion of the locus by repetitive elements almost doubled its size with respect to mouse Smn, in spite of an almost identical protein-coding sequence. Herein, we found that SMN ranks among the human genes with highest density of Alus, which are evolutionary conserved in primates and often occur in inverted orientation. Inverted repeat Alus (IRAlus) negatively regulate splicing of long introns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…After a series of experiments, we con rmed the molecular mechanism that SRSF7 promoted the formation and expression level of circ-PLEKHA5 through binding to PLEKHA5 pre-mRNA. Similar to our nding, RBP-Sam68 has been reported to promote the circularization of SMN exons along with the generation of circ-SMN by binding to SMN pre-mRNA [34] . RBP-QKI binds to the upstream and downstream of SMARCA5 pre-mRNA anking sequence and promotes the cyclization of adjacent exons to form circ-SMARCA5 [31] .…”
Section: Discussionsupporting
confidence: 90%
“…After a series of experiments, we con rmed the molecular mechanism that SRSF7 promoted the formation and expression level of circ-PLEKHA5 through binding to PLEKHA5 pre-mRNA. Similar to our nding, RBP-Sam68 has been reported to promote the circularization of SMN exons along with the generation of circ-SMN by binding to SMN pre-mRNA [34] . RBP-QKI binds to the upstream and downstream of SMARCA5 pre-mRNA anking sequence and promotes the cyclization of adjacent exons to form circ-SMARCA5 [31] .…”
Section: Discussionsupporting
confidence: 90%
“…According to results of previous studies, the CLIP analysis was performed 41 , 42 . After irradiated on ice (100 mJ/cm 2 ), treated cells were lysed using lysis buffer (50 mM Tris, pH 8.0, 100 mM NaCl, 1 mM MgCl 2 , 0.5 mM Na 3 VO 4 , 0.1 mM CaCl 2 , 1% NP-40, 1 mM DTT, RNase inhibitor (Takara, 2313A), and protease inhibitor cocktail (Roche, 5892970001).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth to mention that knocking-down of HNRNPL not only resulted in the reduction of circFAM73A, but also caused a slight increase of FAM73A. A recent study also reported that interfering with SMN circRNAs biogenesis leads to the signi cant rescue of SMN protein [49], implicating the competition between canonical splicing and back-splicing, when back-splicing of exons for circRNA formation is considered as an unusual type of alternative splicing. This competition might explain the increase of linear FAM73A mRNA caused by HNRNPL depletion as it impedes the back-splicing of pre-FAM73A.…”
Section: Discussionmentioning
confidence: 95%